KONSEPSI PERNIKAHAN DALAM ISLAM DAN PERANNYA DALAM MENJAGA ADAB INTERAKSI PRIA-WANITA - Mokhamad Rohma Rozikin (Waskita: Jurnal Pendidikan Nilai dan Pembangunan Karakter, 2019)
Love is natural for human beings. Islam arranges its actualization with marriages. The law of marriage is sunah muakadah, which is a highly recommended action that does not reach mandatory degree. However, marriage is not the goal of life. It is only seen as one of the phases of life that is generally passed by humans as one of the ways of Allah giving good deed opportunities to His servants. As for how to choose a partner, the most important benchmark taught by the Prophet i is the goodness of dien. The process begins with ta’aruf, and if they fit, continues to khitbah (marriage proposal), then proceeds with the marriage contract. In the marriage proposal, among the most important laws are keeping the proposal secret, permission for setting a condition, permission for canceling the proposal, and prohibition for proposing a woman who has received the proposal of another man. As for the distance between the proposal and the marriage contract, no particular nash gives a limit. If the process has led up to the marriage contract, in order to be legitimate, there must be ijab and qabul, the female must be halal to mary, there is a guardian and two Muslim witnesses. If they are legal to be a husband and a wife, then each must understand his or her obligations. In summary, the main duty of the husband is to give dowries, to provide a living, and to care for his wife well. As for the obligations of the wife, the most important thing is obedient to the husband as long as not commanding disobedience to Allah. In addition, the wife also must perform submission/service. If all Shari'as are done ideally, it will create happy and blessed families in the world, so that they deserve to get happiness in the afterlife as well.